Change detection of Sri Ram Sagar Project-1 command area using geospatial tools - Pranay, Panjala (2017)
Sri Rama Sagar Project is I is a multipurpose project constructed across the Godavari River near Pochampad (V) Balkonda (M) Nizamabad (District) during 1964 which is envisaged to irrigate an ayacut of 9, 68,640 Acres covering erstwhile four Districts viz, (Nizamabad, Adilabad, Karimnagar and Warangal) of Telangana and the dam was also meant for generating ( 4*9 MW ) 36MW power of which 3*9MW are already constructed and operational. The main of this study to assess and mapping the changes of crop intensity (i.e., double crop or single crop) under SRSP command area during the irrigated (2000-01, 2010-11) and non irrigated years (2004-05, 2015-16) using coarse resolution multispectral temporal satellite data (MODIS 250m) and their change detection using Geo Spatial Tools. This classification is mainly done by using spectral matching techniques i.e., comparing ideal spectral signatures with NDVI values and Google Earth. This work will help for decision makers to estimate the amount of crop and cropping intensity under the command area.